Integrating Islamic Values into Science Learning in Indonesian Islamic Higher Education: Expectation and Implementation - Fitriyawany, Fitriyawany; Lailatussaadah, Lailatussaadah; Meutiawati, Ida (Universitas Islam Negeri Raden Intan Lampung, 2022)
Integrating Islamic science in universities is very important to be applied to form human resources with character. This study aimed to analyze the expectations and implementation of the integration of Islamic values in lecturers of PTKIN in Aceh. This qualitative descriptive approach involved three deputy deans for academic affairs, nine lecturers, and 12 students from 3 PTKINs in Aceh. Data collection was through an interview, observation, and document analysis (curriculum, books, standard operating procedures (SOPs), and Rencana Pembelajaran Semesters (RPS) or semesterly lesson plans). Data analysis was carried out with an interactive model. The results revealed that integrating Islamic values into the sciences was very diverse in each PTKIN in Aceh. The lecturers had different views and interpretations of the paradigm of integrating Islamic values into learning regarding the boundaries and the concepts applied. Besides, there were no written standard rules and policies (SOP) on integrating Islamic values and limited references used by lecturers in implementing science learning that integrates Islamic values. PTKIN hopes to achieve its vision, goals, and objectives in integrating Islamic values. These objectives can be achieved in science learning. This study concluded that science integration at PTKINs in Aceh had not been consistently carried out, affecting the implemented level that may, in turn, affect the students’ learning. Nevertheless, this study has not examined a set of learning.